Optimization of Ultrasonic-Assisted Extraction Parameters and Antibacterial Activity of Zanthoxylum acanthopodium D.C against Cutibacterium acnes - Rahmi, Eldiza Puji; Pasaribu, Rini Sarah; Harfiani, Erna; Revina, Rika; Septama, Abdi Wira (Pharmacon: Jurnal Farmasi Indonesia, 2025)
Acne is a disease that has affected many populations globally. One of the causes of acne is the presence of acne-causing bacteria, namely Cutibacterium acnes, which is reportedly resistant to several antibiotics. Andaliman fruit (Zanthoxylum acanthopodium DC.) is traditionally used by Indonesian people as a spice which has antibacterial potential. This study aims to evaluate the antibacterial activity of the ethanolic extract of Andaliman fruit against C. acnes using the microdilution method. The extraction method for andaliman fruit was the Ultrasonic-Assisted Extraction with variations in frequency (30, 40, and 50 kHz) and duration (10, 15, and 20 minutes). Phytochemical screening showed the presence of flavonoids, alkaloids, tannins, steroids, and saponins in the extract. The results showed the antibacterial activity of Andaliman fruit extract against C. acnes, with the Minimum Inhibitory Concentration (MIC) observed in the extract with a frequency of 40 kHz and an extraction duration of 10 and 15 minutes at a concentration of 5000 ppm. However, the Minimum Bactericidal Concentration (MBC) test showed negative results, indicating that Andaliman extract did not have a bactericidal effect on these bacteria. Statistical analysis using the Kruskal–Wallis and Dunn tests revealed significant differences (p < 0.05) between extraction treatments and the positive control in MIC and MBC values. These findings indicate that the ethanolic extract of andaliman fruit possesses inhibitory but not bactericidal activity against C. acnes, suggesting its potential as a natural anti-acne agent for further formulation and mechanistic studies.